Prevalence and trends of cigarette smoking among adults with HIV infection compared with the general population in Korea - Boyoung Park; Yoonyoung Jang; Taehwa Kim; Yunsu Choi; Kyoung Hwan Ahn; Jung Ho Kim; Hye Seong; Jun Yong Choi; Hyo Youl Kim; Joon Young Song; Shin-Woo Kim; Hee Jung Choi; et al. (Epidemiology and Health)
OBJECTIVES This study compared the current smoking prevalence among adults with human immunodeficiency virus (HIV) infection to that of the general Korean population and analyzed changes in smoking prevalence and cessation rates from 2009 to 2020. METHODS The study included a total of 10,980 adults with HIV infection who underwent a health screening examination (National Health Insurance Service-National Health Information Database; NHIS-NHID), 1,230 individuals with HIV infection who participated in the Korea HIV/AIDS Cohort (KoCosHIV), and 76,783 participants from the Korea National Health and Nutrition Examination Survey (KNHANES). We estimated the current smoking prevalence and the quit ratio, defined as the ratio of former smokers to ever-smokers. RESULTS In the NHIS-NHID and KoCosHIV studies, the prevalence of current and former smoking among adults with HIV was 44.2% (95% confidence interval [CI], 43.2 to 45.1) and 15.6% (95% CI, 14.9 to 16.3), and 47.7% (95% CI, 43.7 to 51.8) and 16.9% (95% CI, 11.8 to 22.0), respectively. In the KNHANES, these rates were 22.5% and 18.1%, respectively. The standardized prevalence ratio of current smoking among adults with HIV was 1.76 in the NHIS-NHID and 1.97 in the KoCosHIV. Furthermore, the likelihood of quitting smoking was lower among adults with HIV than in the general population (NHIS-NHID: 26.1%; 95% CI, 25.0 to 27.1; KoCosHIV: 26.2%; 95% CI, 20.2 to 32.1; KNHANES: 44.6%; 95% CI, 44.5 to 44.6). Among HIV-positive adults, there was a 1.53% decline in the current smoking rate and a 2.86% increase in the quit ratio. CONCLUSIONS Adults with HIV were more likely to smoke and less likely to quit smoking than the general adult population. Tobacco screening and cessation strategies should specifically target this population.